Efficient decontamination of organic pollutants under high salinity conditions by a nonradical peroxymonosulfate activation system - Chen, Fei; Liu, Lian-Lian; Chen, Jie-Jie; Li, Wen-Wei; Chen, You-Peng; Zhang, Ying-Jie; Wu, Jing-Hang; Mei, Shu-Chuan; Yang, Qi; Yu, Han-Qing (Water research (Oxford), 2021)
•Fe and O codopants substantially accelerated the electron transfer of g-C3N4 for PMS activation.•Efficient BPA removal was achieved at high salinity and within wider pH ranges.•High-valent iron-oxo species and singlet oxygen were identified as two main reactive species.•Nonradical pathways were elucidated based on experimental and theoretical analyses. Peroxymonosulfate (PMS)-based advanced oxidation processes (AOPs) for wastewater treatment have recently attracted widespread interests. However, the degradation of organic pollutants via traditional radical-dominated pathway is severely limited by the side reactions between radicals and the co-existing inorganic anions, especially under high salinity conditions. Herein, an efficient Fe/O co-doped g-C3N4nanosheet catalyst was synthesized to dominantly activate PMS through a dual non-radical pathway with the singlet oxygen and high-valent iron-oxo species (Fe(V)=O). The rapid degradation of model pollutant bisphenol A (BPA) was achieved by dosing PMS (1 mM), catalyst (0.1 g/L) in a simulated high-salt wastewater (≥200 mM) of the developed Fe/O-doped g-C3N4+PMS system with a reaction rate constant of 1204-fold higher than that in g-C3N4+PMS system. The O and Fe co-dopants could reconfigurate the electronic structure of pristine g-C3N4 to produce more non-radical active species. The formed Fe(V)=O played a main role in the BPA degradation by promoting electron transfer from BPA molecule to the “metastable PMS/catalyst complex”, which was verified by electrochemical tests and density functional theory calculations. The auxiliary transient productions of ·OH+SO4·– species were also favorable for the pollutant degradation. Excellent reusability in a wide pH range confirmed the practical application prospects of the Fe/O-doped g-C3N4+PMS system. The successive addition of PMS with a low dosage into the system rich in pollutants was confirmed to favor the PMS utilization. Our work unveils the potential applications of a non-radical dominated process for the decontamination of organic pollutants in saline water.